Double apex - Juniper, Josie (Frontrunners, 2024)
"Phaedra Morgan is one of the best race engineers in Formula 1. She's a math prodigy with dazzling skill, cutting wit, and no patience for matters of the heart. Of course, her job would be a lot easier if she didn't keep butting heads with their team's cocky and infuriatingly hot new driver. Cosmin Ardelean is intense and committed, but as famous for his off-track romantic exploits as his on-track wizardry. Yet his devil-may-care façade conceals a haunted past. When the pair strikes up a secret--and thrillingly forbidden--"arrangement" to improve their communication and bond of trust, the heat of their attraction turns to something more . . . But no secret stays hidden for long in the racing world, and soon things are spinning out of control. With everything on the line, will they be able to strip away all their defenses and go full throttle for a chance at love?"--